Novel Use of Water Immersion in the Management of Exertional Heat Stress. Issue 1 (2021) - Maloy, Wyatt; Hulsopple, Chad
Abstract : ABSTRACT: Heat-related illness can result in increased morbidity and mortality from excessive or prolonged heat exposure that overcomes the body's ability to dissipate the heat load and maintain thermal homeostasis. Postexposure treatment of heat illness has been extensively evaluated along with the role of cold water immersion in the treatment of heat illness. Heat stress mitigation and heat adaptation strategies are currently evolving, including water immersion, to mitigate heat stress and induce heat adaptation. Mitigation strategies are critical to occupations that are not always amenable to heat adaptation because of intermittent and sometimes unexpected introduction to extreme heat exposures complicated by personal protective equipment. Heat adaptation is recommended to mitigate heat-related injuries, and various strategies provide athletes and high-risk occupations a way to adapt to unaccustomed environments. Two approaches to heat stress mitigation and adaptation explored in this article are cold and hot water immersion therapies. These strategies have demonstrated promising results with the potential for minimal disruption in training or work-related schedules.